Traumatic Thoracic Supraspinous Bursitis in Horses: Description of a Clinical Case - Estrada M, Juan (2014)
The paper describes a case of traumatic supraspinous bursitis with a comminutedfracture of thoracic spinous processes T3 to T8 in an equine patient and the techniques used for diagnosis, restriction, sedation, local anesthesia, surgical debridement and partial ostectomy conducted on the standing horse.